Reflecting the Special Autonomy of Papua Province in the Perspective of Law and Human Rights - Roni Sulistyanto luhukay; Tatiek Sri Djatmiati; Emanuel Sujatmoko (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2022)
The practice of administering the particular autonomy government of the Papua Province seems to be centralized even though the state's policy has given the Special Autonomy status to the Papua Province. It can be proven that the authority regulated in the Special Autonomy Law cannot be adequately implemented because central government intervention is very dominant in carrying out certain authorities. Even though the changes in the legislation from Law No. 21 of 2001 to Law No. 2 of 2021 regarding special autonomy for Papua Province also cannot provide many changes regarding the achievement of special autonomy. The birth of Law No. 2 of 2021 concerning the second amendment to Law No. 21 of 2001 concerning special autonomy for the province of Papua. Provide at least 20 amendments to articles regarding the authority of local government, MRP, DPRK, increase in Papua special autonomy funds, expansion of Papua provinces and districts, and establishment of implementing regional regulations of the Special Autonomy Law. The formation of this regulatory change has not provided a concept for protecting indigenous Papuans, considering the potential for centralization of authority to occur still. In addition, this regulatory change also does not provide an overview of the cultural aspects of the indigenous Papuans themselves, and this can be seen by not involving the MRP, which is a representation of the Papuan people. For example, in article 76, paragraphs 1 and 2 regarding the division of the province and district without involving the MRP as a representative of the indigenous Papuans.